Strategy / Roziani Nasir - Nasir, Roziani (Faculty of Art and Design, 2021)
S T R A T E G Y refers to each role in a chess game. The Queen role is highlighted as the power and big role in leading the game. However, to win the game the Queen needs a supporting team besides her. Each character has a role to execute a supporting strategy. In relation to our real life, it symbolises the women’s strong character towards living their challenging life. In the pursuit of the prominent, outstanding and power, the Queen character tends to be bold and lead the strategy to win. In order to win the battle and game, everyone needs to play their roles and follow the strategy. The colours used in this artwork are a combination of warm and cool colours. It is to represent the ups and downs in our life. Sometimes we are in a good position, but other times we may be in the worst situation. But in the end, we need to have a good strategy to encounter to make it in the right path.